A Holistic Approach to Human-Supervised Humanoid Robot Operations in Extreme Environments - Wonsick, Murphy; Long, Philip; Önol, Aykut Özgün; Wang, Maozhen; Padır, Taşkın (Frontiers in Robotics and AI, 2021)
Nuclear energy will play a critical role in meeting clean energy targets worldwide. However, nuclear environments are dangerous for humans to operate in due to the presence of highly radioactive materials. Robots can help address this issue by allowing remote access to nuclear and other highly hazardous facilities under human supervision to perform inspection and maintenance tasks during normal operations, help with clean-up missions, and aid in decommissioning. This paper presents our research to help realize humanoid robots in supervisory roles in nuclear environments. Our research focuses on NASA's humanoid robot, Valkyrie, in the areas of constrained manipulation and motion planning, increasing stability using support contact, dynamic no-prehensile manipulation, locomotion on deformable terrains, and supervised-control interfaces.